Control of ABC Pen Production Raw Materials Using the Material Requirement Planning to Minimize Inventory - Utami, Melly Herliyati; Qurtubi; Setiawan, Danang; Maghfiroh, Meilinda F. N. (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
This study addresses the issue of controlling the inventory of raw materials for pen production at PT. XYZ uses Material Requirement Planning (MRP) to minimize excess inventory. The MRP calculates net requirements, planned receipts, planned order releases, and projected on-hand inventory based on estimated demand, product structure, lot size, lead time, and safety stock. The results categorize 20 raw material components for ballpoint pen products into five levels, determining the optimal quantity and timing for ordering and receiving each component to meet production plans while avoiding excess stock or shortages. This study concludes that the MRP method can significantly optimize inventory management, reducing the risks of overstock and stockouts in the pen production process at PT. XYZ. Consistent application of the MRP method and regular evaluation of supplier capabilities are recommended to ensure efficient and effective raw material inventory planning and control.